A Retrospective Case Series of Synovial Sarcoma of the Upper Extremity. (1st August 2019) - Post, J.; Houdek, M.; Folpe, A. L.; Kakar, S. K.; Wilke, B. K.
Abstract : Purpose . Previous studies have grouped the treatment of axial and appendicular synovial sarcomas. The purpose of this study was to assess the prognostic variables of upper extremity synovial sarcomas (UESS) and compare the outcomes of those who underwent a nononcologic or inadvertent excision prior to definitive resection to those who underwent an initial oncologic resection. Methods . We reviewed the records of 23 UESS treated with definitive surgery at our institution between 1990 and 2014. There were 13 women and 10 men with a median age of 30 years (6–60) and median follow-up of 63 months (15–248). Prognostic variables, recurrence-free survival (RFS), and overall survival (OS) were then assessed. Results . Fifteen patients (65%) had a prior unplanned excision. Five patients required an amputation to obtain local control of disease. There were 3 observed local recurrences and 2 distant metastases at a median of 45 months from presentation. We found no difference in need for amputation, RFS, or OS between those who had undergone a planned excision and those who had an unplanned excision. Conclusion . While we were unable to find a significant difference in outcomes or amputation rates between those who underwent reexcision of a previously unplanned excision and those who underwent an initial planned resection, the high rate of unplanned excision is troubling and should remind practitioners to consider sarcoma in the differential of all upper extremity masses.